A new method for deformation monitoring on H-pile in SMW based on BOTDA. (June 2015) - Ding, Yong; Wang, Ping; Yu, She
Highlights: The H pile can acquire force deformation data automatically by optical fiber. Getting a complete fiber optic monitoring data processing method. Achieving the temperature self-compensation in the pile measurement. Abstract: This paper introduces a new monitoring technology which is characterized by the use of distributed sensing optical fiber to monitor the deformation state of the SMW pile under the stress. With distributed sensing optical fiber attached to the surface inside it, the H-pile is transformed into a pile that has self-sensing capacity. The transformation enables the H-pile to automatically acquire force deformation data such as H-pile flange strain, bending moment, and horizontal displacement. Through the analysis of the H-pile's force structure, a certain method of continuously calculating the pile bending moment, is proposed, with no need to determine the neutral axis' place, and thus achieving temperature self-compensation in the pile measurement. This kind of technology referred to above has been applied in some foundation pit engineering and achieved great success.